Traveling is also writing - Daflon, Claudete (2014)
We propose a reflection about the relationship between voyage and writing for overcome a approach dependent on the definitions of travel literature as genre. We understand, in first place, that the ways as writing and voyage relate each other are relevant andproductive in intellectual upbringing and production processes. From this point of view, we take into account the way how the displacement inscribes itself in text is characterized by the diversity and it revealsthe importance of dislocation’s experiences in literary creation. So we aim explore the implications of the different ways of travelling without worry about a discussion on the specificity of the writing that resultsfrom the travel. We intend to discuss this subject in consonance to ways of writing, specially those of literary nature.